Current sex and age patterns of rock climbing-related injuries treated in emergency departments - Aimee Madsen; Lydia Pezzullo; Ryan M. Nixon; Kevin R. Vincent; Heather K. Vincent (Frontiers in Sports and Active Living, 2025)
Rock climbing is an increasingly popular sport with >7 million participants in the U.S., with fast growth among youth and women. The purpose of this study was to compare sex- and age-related emergent injury patterns due to participation in rock climbing activity. This was a retrospective study of National Electronic Injury Surveillance System (NEISS) data from climbers who sought ED care (N = 1,372; 42.2% female) in U.S. Emergency departments (ED) from 2013 to 2022. The prevalence, type, and anatomical site of climbing injuries by body part and hospital disposition were compared by sex and age bracket [<18 years [pediatric], 18–34 years [adult] and 35–50 years [masters' adult], young] and >50 years [masters' adult, older]) For all climbers, the lower extremity and upper extremity were the most commonly injured sites. Irrespective of sex or age bracket, most injuries occurred in outdoor mountain and rock wall environments. 29.7% were fractures and 19.9% were sprains or strains. 84.6% of patients were treated and released from the ED and 12.3% required admission. For climbers <18 years, 50.0% of injuries were sustained via rock wall, compared to 8.5%–14.7% of other age brackets (p < .05). Compared to climbers aged 35–50 and >50 years, the younger two age brackets experienced more sprains/strains. Female climbers had a higher OR for sprains/strains and lower odds for dislocations than males [OR = 1.40 [1.07–1.82] and OR = 0.59 [0.36–0.95], respectively; both p < 0.05]. Females and climbers aged <18 years more often experience falls in indoor/rock wall environments with short fall heights (≤3.04 m), whereas more males and climbers aged 18–50 years are injured outdoors from greater heights (3.05–15.2 m; p < 0.001). Prevention strategies that can address these vulnerable groups in these environments are warranted to address unique sex and age-related injury diagnoses and fall-related injury risk in the general climbing population.